UNDERSTANDING ATTITUDE TOWARDS CHANGE - Ami Fitri Utami; Moch Sandy Triady (Jurnal Manajemen Indonesia, 2019)
Business dynamics aimed to urge the organization to adapt in order to parlay their competitive advantage. By this, change attempts often inevitable as an effort to keep functioning on the dynamic condition. However, change in an organization is not easy, mainly when it deals with a human within the structure. This research aims to untangle the individual factor, which forms their attitude toward change. By this, the study determines two-variable such self-efficacy and employee’s trust in a leader as a predictor of the employee attitudes toward change. Through the sample of 50 employees from a company which facing a change in business process, it was found that employees’ self-efficacy and trust in leader positively related with the positive attitude toward change. Otherwise, the self-efficacy and trust in leader negatively influence the negative attitude toward change. Through the result, managers might gain insight that gaining trust in the executives and gaining employees’ trust within their ability is imperative to acquire a positive attitude towards change. Keywords—Attitude towards Change, Change, Self-Efficacy, Trust Abstrak Dinamika bisnis akan terus mendorong organisasi untuk melakukan perubahandemi mencapai keunggulan daya saing yang mumpuni. Namun,perubahan bukanlah hal yang mudah diterima oleh anggota organisasi, terutama saat hal tersebut berimplikasi langsung terhadapmereka sebagai individu. Penelitian ini bertujuan untuk memahami bagaimana pengaruh antara keyakinan diri atau self-efficacydan rasa percaya terhadap pemimpin atau trust in leader terhadap respon akan perubahan yang terjadi. Dengan menggunakan sampel sebanyak 50 karyawan dari satu organisasi yang sedang melakukan restrukturisasi ditemjkan bahwa baik rasa keyakinan akan kemampuan diri serta rasa percaya terhadap pemimpin dapat mempengaruhi respon karyawan terhadap perubahan yang ada. Kata kunci—Attitude towards Change, Change, Self-Efficacy, Trust